Real Estate Agents' Personal Work Values Vis-A-Vis Their Perceptions on the Developer's Organizational Values - Mary Rose Tayag; Chere' Yturralde (Research Synergy Foundation, 2025)
The alignment between a developer’s organizational and personal work values underscores the importance of person-organization fit. This study aimed to explore the relationship between real estate agents’ personal work values and real estate developers’ organizational values. The quantitative research employed both descriptive and inferential statistical tools to analyze the frequency and correlations among variables. To establish the correlation between respondents’ perceived competencies and personality traits, Spearman’s Rho and Kruskal-Wallis tests were used. The results indicated that the five subscales of personal work values were deemed extremely important by the respondents, while two subscales were considered essential. Employees prioritized factors such as salary, welfare, awards, honesty, integrity in the workplace, reputation, health, and a safe working environment. Regarding organizational values, employees rated all seven subscales as very important. The findings suggest that organizations must address employee needs to enhance productivity and performance. Moreover, personal work values were significantly related to organizational values, with employees’ values aligning with the organization’s goals. This alignment fosters stronger employee commitment. Understanding and integrating personal and organizational values is essential for improving employee morale and dedication to the organization.